Synthesis and properties of 7,7,12,12-tetramethyl-1,4-dioxacyclotetradecane-8,9,10,11-tetrone - Braunweiler, Christoph; Bethke, Sabine; Rominger, Frank; Gleiter, Rolf (European journal of organic chemistry, 1999)
The fourteen-membered ring of 7,7,12,12-tetramethyl-1,4-dioxacyclotetradecane-8,9,10,11-tetrone (4) was built up from 1,2-bis(2?-chloroethoxy)ethane, two units derived from isobutyric acid and acetylene. Key intermediates were 2,2,11,11-tetramethyl-5,8-dioxadodecane-1,12-diol (8), 7,7,12,12-tetramethyl-1,4-dioxa-9-cyclotetradecyne-2,8-diolprotected by one tetrahydropyran group (15), and 8,11-dihydroxy-7,7,12,12-tetramethyl-1,4-dioxacyclotetradecane-9,10-dione (18). X-ray investigation on single crystals of the (R,S) isomer 18a revealed a transannular interaction between the dioxaethane bridge and the dicarbonyl moiety. Calculations (HF/6-31G*) on 4 predict relatively short distances between the oxygen atoms of the dioxyethane bridge and the (CO)4 part. Investigations by means of cyclic voltammetry, PE and UV/Vis spectroscopy on 4 reveal an interaction between the dioxaethane bridge and the (CO)4 group.
Dedicated to Professor Werner Tochtermann on the occasion of his 65th birthday
Gesehen am 22.10.2020
Keywords: Festschrift